DETECTING GROUPER (EPINEPHELINAE) DIET COMPOSITION AND PREY AVAILABILITY IN RAJA AMPAT CORAL REEFS THROUGH DNA AND eDNA METABARCODING - Hawis Madduppa; Dietriech Geoffrey Bengen; Inna Puspa Ayu; Beginer Subhan; Lalu M Iqbal Sani; Budi Prabowo (SEAMEO BIOTROP, 2023)
Gaining extensive knowledge of prey sources is an essential approach for understanding trophic structure and relationships, especially in highly diverse coral reef ecosystems. Groupers are a major Asian reef fish commodity, making it important to study grouper prey and the trophic relations involved. The wide distribution of groupers across different environments could lead to distinctive predatory behaviour. Therefore, this study was conducted to investigate and compare the taxonomic classification and composition of prey in the diets of two common groupers (Epinephelus areolatus and E. malabaricus) based on DNA metabarcoding of stomach contents and potential prey detection using environmental DNA tools at sites in the coral reefs of Raja Ampat, Indonesia. DNA recovered from the water column comprised taxa from the Arthropoda, Chordata, Cnidaria and Mollusca, several of which were also found in grouper guts, with Cnidaria the most abundant class. Diversity was high for potential prey species in the environment and prey consumed by each grouper species. The high overlap in prey identified from gut contents indicates these two epinephelids have a similar feeding strategy. However, nMDS ordination showed segregation between the prey consumed by each species and potential prey available in the environment. The results indicate a low likelihood of competition between the two grouper species, related to the abundance and wide choice of potential prey in the highly biodiverse Raja Ampat coral reef ecosystem.